Authorizing Marriage? : Canon, Tradition, and Critique in the Blessing of Same-Sex Unions - Mellott, David M.; Sweeney, Meghan T.; Jordan, Mark D. (Book collections on Project MUSE., 2006)
The opponents of legal recognition for same-sex marriage frequently appeal to a "Judeo-Christian" tradition. But does it make any sense to speak of that tradition as a single teaching on marriage? Are there elements in Jewish and Christian traditions that actually authorize religious and civil recognition of same-sex couples? And are contemporary heterosexual marriages well supported by those traditions? As evidenced by the ten provocative essays assembled and edited by Mark D. Jordan, the answers are not as simple as many would believe. The scholars of Judaism and Christianity gathered here e.